Scenario-Based Training and Development Design among the Philippine Local Government Units - Catalino N. Mendoza; Pelagia D.S. Bautista (Zien Journals, 2022)
The study has evaluated the training and development processes of the Philippine Local Government Units (LGUs) particularly on how it affects the level of performances of the employees in different levels. Using the mixed method of research, specifically the Triangulation technique with an intensive statistical application in its evaluation and analysis in different levels of employments and different Local Units of the Philippine Government found out that there is only moderate implementation of the training and development. It only means that there is still a need to develop a training and development program that will enhance the full participations of all employees in fostering an excellent execution of their functions and responsibilities as well as their full potentials in the achievement of the Goals and Objectives of the Local Government Units. Hence, maximize the allocated budgets of the all employees in all aspects of its operations more specifically on enhancing the employees’ customer service with convictions and integrity. The CNM-PDSB Training and Development Model (2021) has been developed to address the need of the Philippine Local Government Units in realizing their visions, missions and goals, hence, giving delights to the customers.
Keywords: Training and Development Design; Local Government Units; Scenario-Based; Triangulation